Monotone Iterative Method for ψ-Caputo Fractional Differential Equation with Nonlinear Boundary Conditions - Zidane Baitiche; Choukri Derbazi; Jehad Alzabut; Mohammad Esmael Samei; Mohammed K. A. Kaabar; Zailan Siri (Fractal and Fractional, 2021)
The main contribution of this paper is to prove the existence of extremal solutions for a novel class of <semantics>ψ</semantics>-Caputo fractional differential equation with nonlinear boundary conditions. For this purpose, we utilize the well-known monotone iterative technique together with the method of upper and lower solutions. Finally, we provide an example along with graphical representations to confirm the validity of our main results.